EVALUATION OF AEROMAGNETIC ANOMALIES OF ABUJA SHEET 186 AND GITATA SHEET 187, NORTHCENTRAL NIGERIA - MONDAY, OGUCHE; CHRISTOPHER, ODEWUMI, SHOLA; STELLA, AKANBI, ETI-MBUK (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Interpretations of High-Resolution Aeromagnetic Data of Abuja Sheet 186 and Gitata Sheet 187, Northcentral Nigeria, were carried out with the aim to determine Curie Point Depth, Geothermal Gradient, Heat Flow, and depth to a magnetic source. Euler Deconvolution method was adopted, and the software used for analysis include: Oasis Montaj Version 8.4, Matlab Version R2020a, Grapher 5, SUFER 11, Georient, and Microsoft Excel. The Total Magnetic Intensity ranges from 32919.5 to 33083.5 nT, and the residual magnetic values range from -392.5 to -171.6 nT. The depth estimates were obtained from the Euler deconvolution technique, using four structural indices of 0.0, 1.0, 2.0 and 3.0. The structural index (0.0) represents contacts and ranges from 60.2 to 318.3m while 1.0 stands for dyke and sill and ranges from 200.7 to 762.2m. Cylinder has structural index of 2.0 and ranges from 206.3 to 1167.0 m. Structural index, 3.0 represents the presence of spheres and ranges from 151 to 1588m. The depth of magnetic sources varies across the study area due to underlying topography. The depth to the Centroid (Zo) ranges from 11.60 to 13.56 km and the depth to the top boundary (Zt) of magnetic sources ranges from 0.311 to 2.16 km. The equivalent curie depth obtained ranges from 22.89 to 25.64 km and could be as a result of the intruded Older Granite suite in the area. The average heat flow (59.32 mWm-2) and geothermal gradients (23.720C km-1) indicate that the heat flows and geothermal gradients were not uniform, which possibly revealed that the magma conduits were randomly distributed and thus could be considered as typical of the continental crust.